Training intensity distribution, training volume, and periodization models in elite swimmers: a systematic review - Gonzalez-Ravé, J. M.; Hermosilla, F.; Mohíno, F. G.; Casado, A.; Pyne, D. B. (International Journal of Sports Physiology and Performance, 2021)
A well-planned periodized approach allows swimmers to achieve peak performance at the major national and international competitions.